Učinki viharja 9.-11. februarja 1984 v Sloveniji - Šifrer, Milan (Geografski zbornik, 1985)
The study deals with the geographical characteristics and the consequences of the violent thunderstorm, which during the February 9-11/1984 devastated parts of Slovenia and especially in the Ljubljana basin and in the Soča area razed some of the places there. According to existing estimates the damage caused by the thunderstorm - suffered by houses and other buildings, electric and telephone lines, forests and orchards - amounts to approximatley 15,700.000 US dollars.
Keywords: 1984; geografija; geography; naravne nesreče; natural disasters; Slovenia; Slovenija; thunderstorm; veter; vihar; wind